Internalisasi Nilai-Nilai Pendidikan Spiritual Dan Sosial Dalam Kegiatan Tahfidzul Qur’an Di PPTQ Al-Munawwar Temanggung - Hanifah Khoirunnisa; Mukromin Mukromin; Chairani Astina (Jurnal Manajemen dan Pendidikan Agama Islam, 2024)
Internalization is essentially a process of instilling something, beliefs, attitudes and personal (personal) values that manifest into social behavior. however, the planting process grows from within a person to the appreciation of a value. The background to the problem of this research is that there are several students who violate regulations and lack norms towards each other, however, with the very rapid development of technology, it is feared that it could disrupt the activities of students in carrying out activities at Islamic boarding schools, especially in Tahfidzul Qur'an activities.This research aims to determine the activities and application of methods, spiritual and social education values, as well as the internalization of spiritual and social education values in Tahfidzul Qur'an activities at PPTQ Al-Munawwar Temanggung. This research uses a qualitative type of research using a descriptive approach. Qualitative research is research with data collection procedures using observation, interviews and documentation methods. in technical data analysis, researchers collect data, reduce data, present data, and draw conclusions. Data validity is checked by data triangulation, namely an examination technique that utilizes untadz or ustadzah, administrators, and students as informants to check or compare the data.The results of this research are that there is no special method for memorizing the Al-Qur'an, the method for memorizing the Al-Qur'an is adjusted to the abilities of each student. There are spiritual education values contained in Tahfidzul Qur'an activities, namely the value of monotheism education, the value of piety education, and the value of moral education. Meanwhile, the social education values of Islamic boarding school students cannot be separated from the intervention of the security council and also the role of Ustadzah religious teachers in the behavior of Islamic boarding school students. There are three strategies used in the process of internalizing the spiritual education values contained in Tahfidzul Qur'an activities, namely habituation, providing an example, and providing mentoring or a personal approach. Meanwhile, the process of internalizing the values of social education in Tahfidzul Qur'an activities, namely by placing the Islamic boarding school in the vicinity of the community, will get used to frequent direct contact, such as in terms of sharing, socializing, community activities, including the main event of the Islamic boarding school, namely the Haflah celebration which is held 2 once a year.The novelty element of this research is that the spiritual and social educational values that are internalized into Tahfidzul Qur'an activities will be able to shape the character of students, because Tahfidzul Qur'an can be used as a tool to increase intelligence, abilities, develop attitudes, increase potential. self and can form students who are responsible, intelligent and creative.